2023
DOI: 10.7150/ijbs.77181
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin epigenetic deregulation in Bladder Cancer associates with acquisition of invasive and metastatic phenotype through epithelial-to-mesenchymal transition

Abstract: Bladder cancer (BlCa) is the ninth most common cancer worldwide, associated with significant morbidity and mortality. Thus, understand the biological mechanisms underlying tumour progression is of great clinical significance. Vimentin (VIM) is (over)expressed in several carcinomas, putatively in association with EMT. We have previously found that VIM promoter methylation accurately identified BlCa and VIM expression associated with unfavourable prognosis. Herein, we sought to investigate VIM expression regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…Vimentin expression requires consideration since we found up-regulation when T24 cells were treated with SFN. This contrasts with reports indicating a correlation between vimentin expression and acquiring an invasive and metastatic bladder cancer phenotype [ 28 ]. Other investigators have demonstrated that spatial vimentin organization is critical for mediating cell migration [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Vimentin expression requires consideration since we found up-regulation when T24 cells were treated with SFN. This contrasts with reports indicating a correlation between vimentin expression and acquiring an invasive and metastatic bladder cancer phenotype [ 28 ]. Other investigators have demonstrated that spatial vimentin organization is critical for mediating cell migration [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Huang' research underscores the oncogenic role of VIM in hepatocellular carcinoma cells (42). Furthermore, research by Sara Monteiro-Reis et al highlights the expression of VIM associates with invasive and metastatic phenotype of bladder cancer (43). Our research discovered that knocking down VIM expression signi cantly curbed the migration and invasion ability of LUAD cell lines, which indicating that VIM was a functional protein to promote the metastasis of LUAD.…”
Section: Discussionsupporting
confidence: 52%
“…For example, H1FX has mainly been highlighted to be associated with cancer to date ( 35 , 36 ), whereas ZFP36L2 was reported to induce apoptosis and inhibit cell proliferation ( 37 , 38 ). VIM is involved in cell attachment, migration, and signal transduction ( 39 ). Here, we separated the exhausted subsets of CD4 + and CD8 + T cells into distinct subclusters via further unsupervised analysis.…”
Section: Discussionmentioning
confidence: 99%